2015
DOI: 10.1080/10852352.2016.1102590
|View full text |Cite
|
Sign up to set email alerts
|

Mental health, well-being, and poverty: A study in urban and rural communities in Northeastern Brazil

Abstract: This article analyzes the relations between mental health and well-being in urban and rural contexts marked by poverty. The analysis takes as its basis a quantitative research conducted with 417 adult inhabitants of two communities, one rural and the other urban, in Northeastern Brazil. The data were constructed using questionnaires composed of sociodemographic data, the Personal Wellbeing Index and Self Report Questionnaire (SRQ-20) scales. We found significant differences between the inhabitants of the rural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
2
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 15 publications
3
20
2
6
Order By: Relevance
“…It is also observed that adolescents seek more psychological assistance for issues like depression, thoughts of suicide and anxiety [7]. Further research is In Australia and Northern Brazil a higher prevalence was measured in the rural areas whilst in Canada and England the reverse was observed [22,36,37]. In the United states as in our study no significant differences were observed between the living areas [38]…”
Section: Resultssupporting
confidence: 46%
“…It is also observed that adolescents seek more psychological assistance for issues like depression, thoughts of suicide and anxiety [7]. Further research is In Australia and Northern Brazil a higher prevalence was measured in the rural areas whilst in Canada and England the reverse was observed [22,36,37]. In the United states as in our study no significant differences were observed between the living areas [38]…”
Section: Resultssupporting
confidence: 46%
“…However, while some studies suggest that the rural environment can have a positive effect on mental well-being [25], especially in developed environments [26,27], others emphasize the negative impact of living isolated in rural communities [28], and the stigma residents may be subject to when seeking help to treat their mental health problems, given that communities are small and social networks do not favor privacy [29]. Psychosocial factors are also a more important determinant of affective or anxiety disorders than the isolation of communities per se [30].…”
Section: Association Between Living Space and Mental Well-beingmentioning
confidence: 99%
“…Besides, GWB could in fact act as a protective factor against psychopathology (McCrae, ). A Brazilian study suggested one of the key issues of mental health services was whether they actually improve the well‐being of the patients for whom psychopathology, especially depression and anxiety, plays an important role (Nepomuceno, Cardoso, Ximenes, Barros, & Leite, ). Based on the previous studies, we will explore how GWB, resilience, and mental health are related among nurses, thus propose the following hypotheses:Hypothesis General well‐being can mediate the relationship between resilience and mental health.Hypothesis The relationship between resilience and mental health is moderated by GWB.…”
Section: Introductionmentioning
confidence: 99%